Prospects for investment in the Chechen Republic - Shatrova, I.; Uzhakhov І. (Ways to Improve Construction Efficiency, 2019)
In this article, the problems of the development of investment activity in the Chechen Republic are presented. The indicated factors limiting the development of the Chechen Republic, as well as the said measures, are based on the above-mentioned problems.